Public-Private Partnership: A Landmark of Mainstream Development Discourse and Why Feminists Should Worry - Rodriguez Enriquez, Corina Maria (2023)
The mainstream development discourse has located the idea of blended finance as a central element.The key argument is that States do not have sufficient resources to meet the investments needed to promote and sustain development. For this reason, it is necessary to combine different sources of financing, including the private sector which appears as a predominant actor. It is from this perspective that a re-launch of public-private partnerships (PPPs) is taking place. PPPs are not a novel form of investment financing, but they have had a vigorous boost in the last decade, hand in hand with the agenda of the Sustainable Development Goals (SDGs).PPPs have been presented as part of the strategy to move from “billions” in Official Development Assistance (ODA) to “trillions” in development invest- ments (World Bank & International Monetary Fund 2015). As the development committee of the World Bank and the IMF stated in 2015 prior to the Third International Conference on Financing for Development, the most substantial development spending happens at the national level in the form of public resources, while the largest potential is from private sector business, finance and investment.This, they argued, is the trajectory from billions to trillions that the world should embrace to finance and achieve the SDGs.Many national governments and regional coalitions have embraced this discourse. In the case of Africa, it is aligned with the vision of “Africa Rising”; that is, the idea that the positive growth rates of many African countries during the first decade of the 2000s indicated a period of economic take-off that would definitively transform the continent and that the process should be sustained with different blended finance strategies.However, many critical voices have emerged which have highlighted that both the Africa Rising narrative and the PPP scheme sugar-coat economic growth strategies that do not guarantee the human rights of the majority, that conceal undesired impacts and serve private interests that are imposed as if they were public interests.In particular, a growing literature has emphasised the controversies that this strategy generates from a feminist perspective.This article aims to present this critical view and to point out the elements that should be taken into account when assessing the PPPs in theory and practice, as well as their implications for inequality gaps and the guarantee of women ́s human rights.The article is organised as follows: in section one, we summarise the different definitions of PPPs and some key conceptual issues.We then proceed in section two to locate the PPP debate in the broader context of development strategies at the global level. In section three, we highlight the main lessons about PPPs from empirical evidence. while in section four we present an in-depth examination of the concerns that may arise when PPPs are viewed from a feminist lens.